The applications of miniprobe endoscopic ultrasonography in the diagnosis and treatment of colorectal submucosal lesions - Zhou, Weizhen; Li, Guang; Liu, Xiao; Gao, Ru; Gao, Yingxin; Hao, Jianyu; Liu, Xinjuan (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the efficacy of miniprobe endoscopic ultrasonography for the diagnosis and adjuvant treatment of patients with colorectal submucosal lesions. Method: The retrospective study was conducted at the Beijing Chao-Yang Hospital, Capital Medical University, China, and comprised data from January 1, 2016, to July 31, 2021, related to patients of either gender with colorectal submucosal lesions who underwent miniprobe endoscopic ultrasonography. The findings were compared with biopsy specimens and clinical diagnoses. Diagnostic features of miniprobe endoscopic ultrasonography were assessed along with its accuracy. Data was analysed using R 4.1.2. Results: Of the 237 patients, 121(51.1%) were female and 116(48.9%) were male. The overall mean age was 55.6+/-12.9 years. Miniprobe endoscopic ultrasonography successfully imaged all 237(100%) colorectal submucosal lesions, and 188(79.3%) had consistent results compared to histopathological findings. The majority of lesions were <10mm 102(43.4%) or 10-19mm 84(35.7%) in size. Those detected with high echogenicity were 126(53.2%) and those with low/low-medium echogenicity were 83(35.0%). Tumour size 10-19mm and uneven echo quality significantly increased the accuracy of miniprobe endoscopic ultrasonography (p<0.05). Conclusion: Miniprobe endoscopic ultrasonography was able to provide precise information about the size, layer of origin, echogenicity and border of colorectal submucosal lesions, and had a high accuracy in the differential diagnosis of such lesions. Key Words: Ultrasonic endoscopy, Colorectal neoplasms, Diagnosis.